ANALISIS BIOMASA DAN CADANGAN KARBON PADA BERBAGAI UMUR TEGAKAN DAMAR (Agathis dammara (Lamb.) Rich.) DI KPH BANYUMAS TIMUR - Zinatul Uthbah; Eming Sudiana; Edy Yani (Scripta Biologica, 2017)
Increased carbon dioxide in the atmosphere causes global climate change seriously. Forests serve as an important asset that can absorb and store carbon in the form of biomass. One type of potential forest as a carbon sink is forests resin. The amount of carbon stored by standing very dynamic and varies according to the age of its standing. Therefore, studies will be needed to determine the effect of age on biomass and carbon stocks stands resin, determine the relationship between age and standing biomass and carbon stocks resin, and knowing the optimum resin stand age in storing biomass and carbon stocks. This research was conducted at the stands of resin RPH Karang Gandul, KPH Banyumas Timur for four weeks in May 2016. The method used is a survey with a sampling technique using cluster random sampling. Stands resin used in the study were classified into five age groups with 5 replicates. Data were analyzed using ANOVA with an error rate of 5% and continued with LSD for further test results were significant and regression analysis to determine the relationship of age with biomass and carbon stocks stands resin. The results showed that the age effect on biomass and carbon stocks stands resin, the relationship formed between the age of stand with biomass and carbon stocks are quadratic, and age optimum in storing biomass and carbon stocks is 35 years.